Tunneling Related Party Lending Phenomenon: Empirical Study on Family Business in Indonesia - Ign.Novie Endi Nugroho; Rahmawati Rahmawati; Bandi Bandi; Agung Nur Probohudono (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
This study examines the effect of family end control with a pyramid structure, RPTs disclosure, internal auditors and independent commissioners on related loan tunneling in Indonesia. This study used a sample of 258 public companies listed on the Indonesia Stock Exchange from 2016-2018. This study provides empirical evidence that the final controller of the family with a pyramid structure is proven to practice tunneling through related loans. The next finding of this study is that the level of disclosure of related transactions can reduce the potential for the practice of tunneling related loans. Another important finding is the failure of the internal control mechanism by internal auditors and independent commissioners which is not able to reduce the potential for related loan tunneling practices in family companies in Indonesia.